Phenotypic Characteristics of Commercial Layer Strains, ISA Brown and Hisex Brown (International Journal of Natural Sciences, 2016)
The study was conducted to observe and compare the phenotypic characteristics of ISA brown and Hisex brown commercial layer strains. A total of 200 birds were examined out of 36000 in a commercial layer farms at Chandonysh upazila (sub-district) of Chittagong district, Bangladesh during the period of July to December, 2013. Observable difference was found in several phenotypic characteristics like plumage, beak, shank, egg, comb color and comb type between ISA brown and Hisex brown. In ISA brown shank length (cm), egg weight (gm) and body weight (gm) was 3.32±0.01, 59.44±0.47 and 1846.60±11.18 respectively where in case of Hisex brown it was 3.11±0.00, 55.82±0.45 and 1769.10±33.90. Significant (P0.05) difference between the strains in respect of shank length, egg weight and body weight. Some innate characteristics of studied strains differentiate them and any improvement program of commercial layer strains should be incorporate production objectives and trait performance of the society.International Journal of Natural Sciences (2015), 5(2) 41-45